Pengaruh e-marketing mix dan mutu pelayanan kesehatan terhadap kepuasan pasien di rumah sakit - Febrina, Dara Meutia Ayu; Pusparani, Kinanti Vionanda; Kusyanto, Fahmi Abdullah; Mubarok, Rizqi; Redjeki, Finny (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: The rapid development of information technology has encouraged hospitals to adopt the E-Marketing Mix to enhance patient access, personalization, and trust. However, service quality remains the key factor in shaping patient satisfaction. Integrating these two aspects is essential to remain competitive in the digital era. Purpose: To analyze the effect of the E-Marketing Mix and healthcare service quality on patient satisfaction and to evaluate the mediating role of patient satisfaction in fostering patient loyalty. Method: This study employed an observational design with a systematic literature review approach. Secondary data were collected from PubMed, Embase, and manual searches (2015–2025) and screened according to inclusion criteria, resulting in 10 eligible articles. A comparative analysis was performed, including synthesis of findings, identification of similarities, and drawing conclusions from the literature. Results: A total of 113 articles were initially identified and screened based on publication year and inclusion criteria, resulting in 10 articles that were included in this literature review. Conclusion: The integration of the E-Marketing Mix with structured service quality improvement programs is a key strategy to create an optimal patient experience, enhance satisfaction and loyalty, and strengthen hospital competitiveness in the digital era.   Keywords: E-Marketing Mix; Hospital; Loyalty; Patient Satisfaction; Service Quality.   Pendahuluan: Perkembangan teknologi informasi mendorong rumah sakit menerapkan E-Marketing Mix untuk meningkatkan akses, personalisasi, dan kepercayaan pasien, namun mutu pelayanan tetap menjadi kunci utama pembentuk kepuasan. Integrasi keduanya penting untuk menghadapi persaingan di era digital. Tujuan: Menganalisis pengaruh E-Marketing Mix dan mutu pelayanan kesehatan terhadap kepuasan pasien, serta mengevaluasi peran kepuasan pasien sebagai mediator terhadap loyalitas pasien. Metode: Penelitian menggunakan desain observasional dengan tinjauan pustaka sistematis. Data sekunder dikumpulkan dari PubMed, Embase, dan pencarian manual (2015–2025), disaring sesuai kriteria inklusi, menghasilkan 10 artikel yang dianalisis secara komparatif. Analisis mencakup sintesis temuan, identifikasi kesamaan, dan penarikan kesimpulan berdasarkan literatur. Hasil: Artikel  yang  didapatkan  pada  sumber  sebanyak  113  dan  diseleksi berdasarkan tahun dan sesuai kriteria inklusi yang ditentukan, sehingga didapatkan sebanyak 10 artikel yang akan digunakan untuk literature review penulis. Simpulan: Integrasi E-Marketing Mix dengan program peningkatan mutu pelayanan merupakan strategi kunci untuk menciptakan pengalaman pasien yang optimal, meningkatkan kepuasan dan loyalitas, serta memperkuat daya saing rumah sakit di era digital.   Kata Kunci: E-Marketing Mix; Kepuasan Pasien; Loyalitas; Mutu Pelayanan; Rumah Sakit.